Analysis of Muzakkar and Muannath in Kawniyyat Words: Sura At-Takwir - Maryam Mokhtar; Aisyah Humairaa Muhammad Faisal; Tg Ainul Farha Tg Abdul Rahman (Universiti Sains Islam Malaysia, 2024)
E-Proceeding :Insan Junior Researcher International Conference(iJURECON)2020 Organized by : Kolej Genius Insan Virtual Conference Page: 258-262